2015
DOI: 10.1007/s11423-015-9397-2
|View full text |Cite
|
Sign up to set email alerts
|

Paraphrasing and prediction with self-explanation as generative strategies for learning science principles in a simulation

Abstract: This study examined the incorporation of generative strategies for the guided discovery of physics principles in a simulation. Participants who either paraphrased or predicted and self-explained guided discovery assignments exhibited improved performance on an achievement test as compared to a control group. Calibration accuracy (the correspondence between judgments of performance and actual performance) was also improved for the two generative strategy groups. The thoroughness of generative content and qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Like other qualitative descriptions of self-explanations, our explanations varied primarily according to engagement and application of prior knowledge (Morrison et al, 2015;Rittle-Johnson et al, 2017;Roy & Chi, 2005). Thus, it appears that the variations in computer-based self-explanations are similar to those observed in other self-explaining formats, but it may be easier for students to avoid engagement with self-explaining on a computer.…”
Section: Discussionmentioning
confidence: 99%
“…Like other qualitative descriptions of self-explanations, our explanations varied primarily according to engagement and application of prior knowledge (Morrison et al, 2015;Rittle-Johnson et al, 2017;Roy & Chi, 2005). Thus, it appears that the variations in computer-based self-explanations are similar to those observed in other self-explaining formats, but it may be easier for students to avoid engagement with self-explaining on a computer.…”
Section: Discussionmentioning
confidence: 99%
“…By linking general concepts and skills to the specific elements of the problem at hand through inferences, learners increase their understanding (Rau et al, 2015). As learning progresses and learners understand new information, they go through an integrated process that links, distinguishes, organizes, and structures all the information they have learned (Morrison, Bol, Ross & Watson, 2015). This process is essential for problem-solving (Jonassen, 2000): by coordinating external information and existing knowledge, integration leads to better understanding (Wittrock, 1989).…”
Section: The Focus Of Self-explanation Promptsmentioning
confidence: 99%
“…Self‐explanation activities involve two learning mechanisms: the scaffolding provided to the students by identifying gaps in their understanding within the example, and the construction and repair processes of the student's mental model (Chi, 2000; Morrison et al, 2015). Since the worked examples often miss part of the information for the problem‐solving process, self‐explaining allows students to generate inferences that lead to fill in these omissions (Chiu & Chi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chi and Bassok (1988) concluded that outstanding students tactically add knowledge fragments in their written self‐explanation to physics examples. Morrison et al (2015) found that students who worked on prediction, self‐explanation, and paraphrasing activities performed better than those in a control group who studied the materials without a specific generative strategy. These students also showed higher ratings of mental effort and cognitive loads.…”
Section: Introductionmentioning
confidence: 99%